The Role of Transformational Leadership in Change Management in Local Government Organizations - Mandasari, Dwi Arini; Ismail, Iriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to determine the influence of Transformational Leadership on Change Management in Regional Government Organizations, and to find out how much influence Transformational Leadership has on Change Management in Regional Government Organizations. This research is often discussed, but has not specifically discussed the relationship between the two, especially within local government. The results of the research are that Transformational Leadership has a significant and positive influence on Change Management in Regional Government Organizations and the magnitude of the influence of the transformational leadership variable on change management is 52.9%, of which the remaining 47.1% is influenced by other variables not discussed in this research